Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.3402/jchimp.v3i3-4.21362
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and acceptability of a five-station multiple mini-interview model for residency program recruitment

Abstract: BackgroundStandard interviews are used by most residency programs in the United States for assessment of aptitude of the non-cognitive competencies, but variability of interviewer skill, interviewer bias, interviewer leniency or stringency, and context specificity limit reliability.AimTo investigate reliability and acceptability of five-station multiple mini-interview (MMI) model for resident selection into an internal medicine residency program in the United States.SettingOne independent academic medical cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…The reliability of 0.94 in our exercise is understandable as in our MMI, 447 candidates were rated using six identical circuits over several sessions. It is reassuring to note that a similar 5-station MMI which rated 237 candidates also reported a similar reliability of > 0.9 (33). Despite the reassuring data, we will still consider adding more stations to future MMIs as long as feasibility permits, as common assessment sense would suggest that it will increase the validity and reliability further.…”
Section: Validity and Reliabilitymentioning
confidence: 93%
“…The reliability of 0.94 in our exercise is understandable as in our MMI, 447 candidates were rated using six identical circuits over several sessions. It is reassuring to note that a similar 5-station MMI which rated 237 candidates also reported a similar reliability of > 0.9 (33). Despite the reassuring data, we will still consider adding more stations to future MMIs as long as feasibility permits, as common assessment sense would suggest that it will increase the validity and reliability further.…”
Section: Validity and Reliabilitymentioning
confidence: 93%
“…The MMI was found to be reliable (r=0.7-0.85) using individual interviewers in 6-12 stations that ranged from 5.5-10 minutes each (Eva et al, 2004;Harris & Owen, 2007;Hecker et al, 2009;Hofmeister, Lockyer, & Crutcher, 2009;Roberts et al, 2008). In addition, the MMI demonstrated predictive validity for future assessments of non-cognitive performance (Eva et al, 2009;Lemay, Lockyer, Collin, & Brownell, 2007;Reiter, Eva, Rosenfeld, & Norman, 2007;Roberts et al, 2008), was acceptable to applicants and interviewers (Diaz Fraga, Oluwasanjo, Wasser, Donato, & Alweis, 2013;Humphrey, Dowson, Wall, Diwakar, & Goodyear, 2008;Kumar, Roberts, Rothnie, du Fresne, & Walton, 2009;Razack et al, 2009) and cost-effective (Rosenfeld, Reiter, Trinh, & Eva, 2008), leading to its widespread adoption as an interviewing format in Canada, the United States, and Australia (Eva et al, 2004;B. Griffin & Wilson, 2012;Kreiter, Yin, Solow, & Brennan, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Inherent problems of traditional interviews are the variability in the interviewers' communication skills, bias, tolerance, and personality. [1][2][3][4][5] Many studies have shown that traditional interviews have poor interrater reliability and perceived gender and cultural bias, with inadequate reliability and questionable validity. [1][2][3][4][5][6] The multiple mini interview (MMI) is a standardized, validated selection process that consists of several stations, each of which assesses different aspects of the applicants; the MMI is used in medical schools in Canada and has spread to other nations.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Many studies have shown that traditional interviews have poor interrater reliability and perceived gender and cultural bias, with inadequate reliability and questionable validity. [1][2][3][4][5][6] The multiple mini interview (MMI) is a standardized, validated selection process that consists of several stations, each of which assesses different aspects of the applicants; the MMI is used in medical schools in Canada and has spread to other nations. [1][2][3][4][5][6][7][8] The behavioral format utilizes questions that relate to past behaviors and performance as a way to identify latent professionalism characteristics, and this approach is predictive of future behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation